Eliciting teachers’ understanding and their reported practices on school-based formative assessment: Methodological challenges - Hasim, Zuwati; Di, Shi; Barnard, Roger (Indonesian Journal of Applied Linguistics, 2018)
Ministries of Education in many countries have adopted various forms of school-based assessment (SBA) to replace (for example, New Zealand) or complement (for example, England, Australia and Malaysia) more conventional forms of assessment such as tests and examinations. Central to these alternative approaches to SBA is formative assessment. In recent years, a body of research has been built investigating various aspects of SBA in Malaysia, but there has been a dearth of studies exploring what practising teachers believe and do regarding implementing formative assessment in their own classrooms. The present article reports some of the findings of a case study in which ten Malaysian primary school teachers of English were interviewed to identify the extent of their understanding of formative assessment and their reported practices of providing feedback in an SBA environment. Initially, the teachers revealed a general lack of understanding of the difference between formative and summative assessment. In such a situation, it would seem that the teachers are unready to implement SBA at the present stage, despite it having been mandated in Malaysian schools since 2011-12. However, later in the interview, they reported implementing various forms of feedback, some of which might be regarded as formative. There is a need, therefore, to differentiate between teachers’ explicit knowledge and their implicit understanding of matters such as formative feedback. The inherent limitations of self-report data emerging from interviews will be discussed and how these might be overcome.